AKTIVITAS ANTIBAKTERI (BACTERIOSTATIC DAN BACTERICIDAL) FILTRAT DAN SEDIMEN AIR PERASAN DAUN VALOAK TERHADAP BAKTERI Salmonella typhi - Abdul Majid; Nikmah Majid (CHMK Applied Science Journal, 2020)
ABSTRACT The purpose of this research is to know the activity of the antibacterial filtrate and sediment from the juice of the leaves valoak (Sterculia comosa Wallich) bacteriostatic or off bactericidal on the Salmonella typhi. This is the experimental-laboratory research, the treatment included five (5) filtrate and sediment concentration of the juice of the leaves valoak (Sterculia comosa Wallich) is: A = 100%, B = 80%, C = 60%, D = 40%, E = 0 %, and each with five (5) replications.The results showed that treatment of the activity of the antibacterial filtrate and sediment from the juice of the leaves valoak (Sterculia comosa Wallich) off bactericidal on the Salmonella typhi bacteria at a concentration of 80%. Keywords : Filtrate, Sedimant, Sterculia comosa Wallich, Salmonella typhi